Effect of a pulsed electron beam irradiation on the structural and phase state and hydrogen degassing of ZR-1NB alloy - Stepanova E. N. Ekaterina Nikolaevna; Grabovskaya G. P. Galina Petrovna; Mishin I. P. Ivan Petrovich; Teresov A. D. Anton Dmitrievich (2014, 2014)
Title screen